PERBEDAAN MOTIF PENGGUNAAN BUKU LANGKA TERCETAK DI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA BERDASARKAN GENDER - Raihanah Athaya; Danang Dwijo Kangko; Elfitri Kurnia Erza (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2021)
The motives for the use of media are different, one of the factors is gender. This study aims to see the motives for using printed rare books in the National Library of Indonesia and whether there is a different motive for using printed rare books between men and women. The population of this research is active e-mail users, registered members of the National Library of Indonesia, and who have read printed rare books. This type of research is quantitative using the Uses and Gratification method. The sample size is 75 respondents. The sampling technique used was proportional stratified random sampling. Based on the results of the analysis, there are 4 motives for using printed rare books, namely Information Motive, Personal Identity Motive, Integrity Motive and Social Interaction, and Entertainment Motive. The total results show that the most dominant motive for using rare books printed in the National Library of Indonesia is information on motives, with a proportion of 87% and 83% to satisfy their curiosity and to learn about events and environmental conditions after reading printed rare books. The lowest motive is the personal identity motive with a proportion of 70% and 67% to adapt the behavior and behavior values obtained when reading rare books printed in everyday life and ready to see information about events or environmental conditions in the past, latest or rare. The results of hypothesis testing show that H1 is rejected and H0 is accepted with a sig 0.05, namely 0.869 0.05, so it can be said that there is no difference in motives for using rare books in the National Library of Indonesia between men and women.